Ultrasound potential in sarcopenic obesity diagnosis: a literature review - D. A. Tsygankov; K. E. Krivoshapova; D. P. Tsygankova (Российский кардиологический журнал, 2023)
With an increase in the average life expectancy of the population, the prevalence of sarcopenic obesity (SO) is correspondingly growing. Existing definitions of SO are based on description of sarcopenia and obesity, but there is currently no consensus defining thresholds for either of these conditions, making an accurate diagnosis difficult. At the same time, its treatment is important to prevent disability in the elderly. In this regard, the purpose of this review was to analyze the ultrasound potential for SO diagnosis. Since ultrasound is cheaper, more portable, and more accessible than other methods, it has the potential to be widely used as a clinical screening tool for identifying people with SO. Also, this method can be used to diagnose obesity, thereby leveling the errors in body mass index.